It happens all the time : a novel - Hatvany, Amy, 1972- (Atria Books, an imprint of Simon & Schuster, Inc., 2017)
"Amber Bryant and Tyler Hicks have been best friends since they were teenagers--trusting and depending on each other through some of the darkest periods of their young lives. And while Amber has always felt that their relationship is strictly platonic, Tyler has long harbored the secret desire that they might one day become more than friends. Returning home for the summer after her college graduation, Amber begins spending more time with Tyler than she has in years. Despite the fact that Amber is engaged to her college sweetheart, a flirtation begins to grow between them. One night, fueled by alcohol and concerns about whether she's getting married too young, Amber kisses Tyler. What happens next will change them forever."--Amazon.com.